PANTUN DALAM TRADISI ANTAR CIKRAM PADA PRAPERKAWINAN MASYARAKAT MELAYU PEMANGKAT - Nursita, Nursita; Sulissusiawan, Ahadi; Wartiningsih, Agus (Universitas Tanjungpura, 2023)
This research aims to determine the results of the analysis of the pantun in antar cikram tradition on the premarriage of the Pemangkat Malay community. The research method used is descriptive with the form of qualitative research. This research uses structural approach, semiotic approach, and sociological approach to literature. The data source of this research is pantun in antar cikram tradition spoken by pantun speakers. Data collection techniques using direct observation techniques. The results of this research are the structure, meaning, and function of the pantun in antar cikram tradition. The structures found were diction, imagery, concrete words, figurative languange, rhyme, theme, feeling, tone and atmoshphere, and mandate. The meanings found are denotative meanings and connotative meanings. The functions found are recreational, didactic, aesthetic, morality, and religious functions. Pantun in antar cikram tradition on the premarriage of the Pemangkat Malay community there are 32 pantun with the presentation of text editing and text translation at two antar cikram tradition events. Based on results of data analysis, there are 217 data on the structure of the pantun, 32 data on the meaning of the pantun, and 26 data on the function of the pantun.